INSTRUMENTY FINANSOWE NOTOWANE NA RYNKU ‘CATALYST’ – WYBRANE ZAGADNIENIA PRAWNE - Piotr Zapadka (Zeszyty Prawnicze, 2016)
The Financial Instruments Listed on the Catalyst Bond Market: Selected Legal Aspects Summary The Catalyst Bond Market, which was launched on 30 September 2009, comprises four trading platforms which operate on the transaction platforms of the Warsaw Stock Exchange and BondSpot. Two of them can be classified as multilateral trading facilities (MTF) (in the meaning of art. 3 point 2 of the Trading in Financial Instruments Act of 29 July 2005) and the other two are an off-exchange regulated market (in the meaning of art 15 paragraph 1 point 2 of the Trading in Financial Instruments Act of 29 July 2005). Although the name of this market may suggest otherwise, bonds are not the only subject of the market transactions on the Catalyst Bond Market. This simplification may be due to social communication and marketing requirements. Besides bonds issued by companies (corporate bonds) and co-operative banks (co-operative bonds), other kinds of debt securities are listed on this market (i.e. issued by mortgage banks, cities, or even the State Treasury). Thus it would be more accurate to call Catalyst an organised debt securities market. Debt securities can be much more attractive for an issuer than equity securities. The issuer may for some reason wish to discourage the buyer of securities from exercising his ownership rights, e.g. by voting at the shareholders’ general meeting. The aim of this article is to describe this kind of organised debt securities market from the legal perspective, taking into consideration the growth of the debt market in the modern economy.